2019
DOI: 10.1111/ecc.12984
|View full text |Cite
|
Sign up to set email alerts
|

Family resilience and psychological well-being among Chinese breast cancer survivors and their caregivers

Abstract: Walsh's family resilience theory indicated that families could foster resilient outcomes among their members when they are facing changes or crises. However, little is known about family resilience and psychological well‐being among Chinese breast cancer survivors and their caregivers. Therefore, this study aimed to examine the direct and indirect relationships between family resilience, breast cancer survivors' post‐traumatic growth (PTG), quality of life (QOL), and their principal caregivers' caregiver burde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 41 publications
7
82
2
3
Order By: Relevance
“…Strong family support may be bene cial to improve the patient's resilience. Considering the signi cance of family networks in China, it is necessary to further focus on enhancing family resilience for the patients in breast cancer care [38,39]. However, patients with lower optimism and higher negative CS (i.e., avoidance and resignation) scores are a concerning group.…”
Section: Discussionmentioning
confidence: 99%
“…Strong family support may be bene cial to improve the patient's resilience. Considering the signi cance of family networks in China, it is necessary to further focus on enhancing family resilience for the patients in breast cancer care [38,39]. However, patients with lower optimism and higher negative CS (i.e., avoidance and resignation) scores are a concerning group.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Li, Qiao, Luan, Li, & Wang, (2019) showed that resilience of caregivers of cancer patients contributed to QOL of caregiver burden. These previous studies show that resilience may be related to QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos apontam que as equipes designadas para cuidar do paciente com ferida neoplásica sentem-se pessoalmente angustiadas pelo sofrimento causado pela ferida, frustradas por não serem capazes de obter curativos adequados para as necessidades de seus pacientes ou não por terem tempo suficiente para ouvir, experimentando serntimentos de raiva, falta de esperança, frustração, inadequação, tristeza e culpa (Lazelle-Ali, 2007;Li, Qiao, Luan, Li, Wang & 2019).…”
Section: Resiliência Do Paciente Com Ferida Tumoral Malignaunclassified